PENGARUH RETURN ON ASSET, LOAN TO DEPOSIT RATIO DAN NET INTEREST MARGIN TERHADAP EARNING PER SHARE SAHAM PT. BANK MANDIRI, TBK - Imron Rosadi (Fakultas Ekonomi Universitas Borobudur, 2019)
This study aims to analyze how much influence the Return On Assets, Loan To DepositRatio and Net Interest Margin to Earning Per Share shares of PT.Bank Mandiri, Tbk 2005-2017both simultaneously and partially. The population of this research is financial report data ofPT.Bank Mandiri using quarter 2005-2017 data. The sample of this research use purposivesampling method. The sample in this research is 52 sample time series data. The type of data usedis secondary data derived from the official bank website ir.bankmandiri.co.id and also IDX.Technical analysis using multiple linear regression analysis.The result by using F test shows that the ratio of Return On Asset, Loan To Deposit Ratioand Net Interset Margin simultaneously have a positive and significant effect on Earning PerShare. The result by using t test indicates that the ratio of Return On Asset and Loan To DepositRatio partially have a positive and significant influence on Earning Per Share, while the ratio ofNet Interest Margin partially has no positive and significant effect on Earning Per Share. Thecoefficient of determination shown from the adjusted R-square value of 0.946503 or 94.65%. Thismeans that the variable Retun On Assets, Loan To Deposit Ratio and Net Interest Margin able toexplain the variable Earning Per Share, while the rest of 5.35% explained by other variables.